Intra-Amniotic LPS Induced Region-Specific Changes in Presynaptic Bouton Densities in the Ovine Fetal Brain. (31st August 2015) - Strackx, Eveline; Jellema, Reint K.; Rieke, Rebecca; Gussenhoven, Ruth; Vles, Johan S. H.; Kramer, Boris W.; Gavilanes, Antonio W. D.
Abstract : Rationale . Chorioamnionitis has been associated with increased risk for fetal brain damage. Although, it is now accepted that synaptic dysfunction might be responsible for functional deficits, synaptic densities/numbers after a fetal inflammatory challenge have not been studied in different regions yet. Therefore, we tested in this study the hypothesis that LPS-induced chorioamnionitis caused profound changes in synaptic densities in different regions of the fetal sheep brain. Material and Methods . Chorioamnionitis was induced by a 10 mg intra-amniotic LPS injection at two different exposure intervals. The fetal brain was studied at 125 days of gestation (term = 150 days) either 2 (LPS2D group) or 14 days (LPS14D group) after LPS or saline injection (control group). Synaptophysin immunohistochemistry was used to quantify the presynaptic density in layers 2-3 and 5-6 of the motor cortex, somatosensory cortex, entorhinal cortex, and piriforme cortex, in the nucleus caudatus and putamen and in CA1/2, CA3, and dentate gyrus of the hippocampus. Results . There was a significant reduction in presynaptic bouton densities in layers 2-3 and 5-6 of the motor cortex and in layers 2-3 of the entorhinal and the somatosensory cortex, in the nucleus caudate and putamen and the CA1/2 and CA3 of the hippocampus in the LPS2D compared to control animals. Only in the motor cortex and putamen, the presynaptic density was significantly decreased in the LPS14 D compared to the control group. No changes were found in the dentate gyrus of the hippocampus and the piriforme cortex. Conclusion . We demonstrated that LPS-induced chorioamnionitis caused a decreased density in presynaptic boutons in different areas in the fetal brain. These synaptic changes seemed to be region-specific, with some regions being more affected than others, and seemed to be transient in some regions.